CORONAVIRUS-A VIRUS IN LEARNING - NIHARIKA, D.; NIHARIKA, B.; AISHWARYA, T.; NIKITHA, A.; BUTOOL, RABIA; IBRAHIM, MANAL; DHARAKESWARE, R. (International Journal of Current Pharmaceutical Research, 2020)
Viruses can infect almost all the types of life forms, from animals, plants to microorganisms. They are found in almost every ecosystem on Earth and are the most numerous types of biological entity. The present pandemic on Earth due to SARS COV 2, coronavirus has given a big jolt to the scientific community and created a deep curiosity in us to understand the virus and its interaction biochemically in humans. We did a small project by researching and compiling the information about its outbreak and host-pathogen interactions. To understand this pandemic COVID 19 and the virus, we as students learnt the structural morphology of virus and its role in the host-pathogen interaction. We used several online platforms for our study like PubMed, Scopus, WHO, ICMR and CDC Websites.